Cost and Effectiveness of Accommodations in the Workplace: Preliminary Results of a Nationwide Study - Hendricks, D.J.; Batiste, Linda C.; Hirsh, Anne; Schartz, Helen; Blanck, Peter (Disability Studies Quarterly, 2005)
This article provides a description and brief history of the Job Accommodation Network (JAN), a project funded by the U.S. Department of Labor's Office of Disability Employment Policy. Preliminary results from JAN's customer satisfaction survey are presented. At present, 778 employers and 882 individuals with disabilities have been interviewed. The findings to date indicate that a broad spectrum of business types use JAN's services. JAN customers reported that implementation of worksite accommodations would significantly reduce the individual's level of limitation due to the disability. Importantly, JAN customers reported having made highly effective accommodations at very little or no cost. Employers who were interviewed said slightly over half (50.5%) of the accommodations they implemented following discussion with JAN had been at no cost. For those employers who did experience some cost, the median dollar value was $600.